Penerapan Aplikasi Miracle Salon - Megaria - Purba; Dame Esterlina br Jabat; Veronika Saragih (STMIK Budi Darma, 2022)
The application of the Miracle Salon application is the result of research with the output of appropriate technology software that will be applied to user partners, namely Miracle Salon which is engaged in the Beauty business. The partner location is next to the AMIK Widyaloka campus, Medan, Jalan TB Simatupang No. 161 A, Medan Sunggal, North Sumatra. The problem faced by partners so far is that promotions are carried out only by word of mouth so that people do not know and know less about the miracle salon. Because the promotion is only done by word of mouth, the fans are only people around the miracle salon environment. To introduce partners more broadly, our Devotion team donated the Miracle Salon Application to be used by partners through mentoring and training for partners. This service is carried out starting from good relations with partners, analyzing ongoing systems, designing, and training partners to skillfully use development and maintenance. With the completion of the training, it is hoped that partners will have the skills to use the application so that miracle salon promotions are known to the wider community and more customers.